How to Train Your Health: Sports as a Resource to Improve Cognitive Abilities in Cancer Patients - Sebri, Valeria; Savioni, Lucrezia; Triberti, Stefano; Mazzocco, Ketti; Pravettoni, Gabriella (Frontiers in Psychology, 2019)
From a cognitive-psychological perspective, physical exercise (PE) and sports represent an interesting tool to improve people’s cognitive abilities. One field of application for such tool is decision making (DM) support in chronic patients, cancer patients and survivors in particular. On the one hand, cancer patients and survivors have to continually take important decisions about their own care (e.g., treatment choice; changes in lifestyle), in collaboration with caregivers and health providers; on the other hand, side effects of treatment may provoke detriments in cognitive abilities, such as attention, which make the health DM tasks even more demanding, complex, and emotionally disruptive for patients. Since cancer patients have to engage in healthy activities both for improving their own quality of life and for sustaining the effects of medications, the clinical advice of engaging in sport and PE is becoming more and more widespread within interventions. However, while sports are usually seen as healthy physical activities, their impact on cognitive abilities is mostly overlooked in the literature. The hypothesis of the present work is that sports could be fully exploited in their potential as focused exercises for cognitive ability training, in the field of cognitive training for chronic patients specifically. Indeed, literature shows that different sports (e.g., individual or team-based) influence and possibly augment cognitive abilities such as focused and divided attention, working memory, and DM under time constraints. Moreover, besides providing training for cognitive abilities, the experience of sports may represent an opportunity to explore, train and sharpen DM abilities directly: we identify five ways in which sport experience may influence DM processes, and provide indications for future research on the topic.